2007
DOI: 10.1073/pnas.0703133104
|View full text |Cite
|
Sign up to set email alerts
|

A gene from the cellulose synthase-like C family encodes a β-1,4 glucan synthase

Abstract: Despite the central role of xyloglucan (XyG) in plant cell wall structure and function, important details of its biosynthesis are not understood. To identify the gene(s) responsible for synthesizing the ␤-1,4 glucan backbone of XyG, we exploited a property of nasturtium (Tropaeolum majus) seed development. During the last stages of nasturtium seed maturation, a large amount of XyG is deposited as a reserve polysaccharide. A cDNA library was produced from mRNA isolated during the deposition of XyG, and partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
268
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(277 citation statements)
references
References 25 publications
4
268
0
5
Order By: Relevance
“…We have examined the monosaccharide composition of the endosperm over the course of development, applied the recently generated xyloglucan antibody to early endosperm development, and modified our approach to studying arabino-(1→4)-b-D-xylan using the LM11 antibody. Previous studies identifying genes involved in the synthesis of cell wall polysaccharides have shown that transcript accumulation correlates with the time of polysaccharide synthesis and deposition (Pear et al, 1996;Doblin et al, 2001;Dhugga et al, 2004;Brown et al, 2005;Persson et al, 2005;Cocuron et al, 2007;Mitchell et al, 2007). By coupling our immuno-EM observations with transcript profiles of candidate cell wall synthesis genes, we can now infer which subfamily members of these gene families is functional during key stages of endosperm development.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…We have examined the monosaccharide composition of the endosperm over the course of development, applied the recently generated xyloglucan antibody to early endosperm development, and modified our approach to studying arabino-(1→4)-b-D-xylan using the LM11 antibody. Previous studies identifying genes involved in the synthesis of cell wall polysaccharides have shown that transcript accumulation correlates with the time of polysaccharide synthesis and deposition (Pear et al, 1996;Doblin et al, 2001;Dhugga et al, 2004;Brown et al, 2005;Persson et al, 2005;Cocuron et al, 2007;Mitchell et al, 2007). By coupling our immuno-EM observations with transcript profiles of candidate cell wall synthesis genes, we can now infer which subfamily members of these gene families is functional during key stages of endosperm development.…”
Section: Discussionmentioning
confidence: 84%
“…Although a definitive role for xyloglucan during early development cannot be deduced from this study, it is of interest that the low levels of xyloglucan often seen in the cell walls of the commelinoid monocots appears to be associated with young and/or expanding cells, although xyloglucan is present in the mature endosperm cell walls of rice (Kato et al, 1982;Nevins, 1984, 1991;Gibeaut et al, 2005) and has recently been reported to be present in mature tissues of specific cell types in some members of the Poales (Brennan and Harris, 2011). Cocuron et al (2007) proposed that the CSLC proteins function is to synthesize the xyloglucan backbone although Dwivany et al (2009) have also proposed a role for some CSLC family members in the synthesis of cellulose in certain specialized cell types. Quantitative reverse transcription-PCR analysis undertaken here showed that the abundance of barley CSLC gene transcripts was extremely low (data not shown), consistent with the low levels of xyloglucan (Fincher, 1975;Bacic and Stone, 1981b).…”
Section: Xyloglucanmentioning
confidence: 82%
See 2 more Smart Citations
“…Surprisingly few Csl genes have been assigned a specific function in plant cell wall biosynthesis. Members of the CslA subfamily encode (1,4)-b-D-mannan synthases (Dhugga et al, 2004;Liepman et al, 2007), and the CslC group is believed to encode an enzyme that directs the synthesis of the (1,4)-b-D-glucan backbone of xyloglucans (Cocuron et al, 2007). Using a comparative genomics approach, Burton et al (2006) showed that a cluster of the monocot-specific CslF genes in rice is located in a genomic region corresponding to one containing a major quantitative trait locus (QTL) for grain (1,3;1,4)-b-D-glucan content in barley (Hordeum vulgare).…”
mentioning
confidence: 99%